Society in Na. Muthukumar's Poems - S, Esther Mary (International Research Journal of Tamil, 2022)
Tamil literature paves the way for individual life. The individual also lives together with the society. Literature is changing according to social change. Individual human condition sand individual human morals adjust social thoughts. Muthukumar has dealt more with social concepts in his poems. If society is to prosper, family relationships must prosper. He has properly created this idea in his poems. His poems are very realistic and simple. His works are structured in such a way that even common people can easily understand them. Beyond individual power, literature creates a new way of life.